Wrist Swelling in Kienböck's Disease - Ichinose, Hirofusa; Nakamura, Ryogo; Nakao, Etsuhiro; Shinohara, Takaaki; Tatebe, Masahiro; Yamada, Harumoto (Journal of Wrist Surgery, 2018)
Background and Purpose Wrist swelling is a frequent clinical manifestation of Kienböck's disease, but no study has reported the site and pathology of wrist swelling in this disease. The aim of this study is to elucidate the site and pathology of wrist swelling in Kienböck's disease.Materials and Methods Dorsal and palmar soft tissue thicknesses of the wrist were measured on standard lateral radiographs of the wrist in 26 patients with Kienböck's disease and 30 subjects without intra-articular lesion. Axial magnetic resonance imaging (MRI) views were examined to detect the site of swelling. The dorsal capsular ligament in three patients with Kienböck's disease underwent histological examination.Results Radiographic study confirmed dorsal wrist swelling in 24 of 26 (92%) patients examined compared with the contralateral unaffected wrists. MRI demonstrated thickening of the dorsal capsular ligament and extensor layer with synovial proliferation. Histological examination revealed nonspecific chronic inflammation.Conclusion Dorsal wrist swelling in Kienböck's disease is a common manifestation and constitutes a part of pathology of Kienböck's disease, although further study is required to clarify the relation between wrist swelling and etiology of Kienböck's disease.Level of Evidence This is a Level III study.
Keywords: wrist swelling; Kienböck's disease; inflammation; capsulitis; synovitis